EFFECT OF NCO/OH RATIO AND MOLD SYSTEM ON PHYSICAL AND MECHANICAL PROPERTIES OF RIGID POLYURETHANE FOAM BASED ON PALM OIL - Evi Triwulandari; Agus Haryono; Wiwik Pudjiastuti (Jurnal Sains Materi Indonesia, 2011)
EFFECT OF NCO/OH RATIO AND MOLD SYSTEM ON PHYSICAL AND MECHANICAL PROPERTIES OF RIGID POLYURETHANE FOAM BASED ON PALM OIL. A new kind of rigid polyurethane foam (RPUF) was synthesized from palm oil based polyol. Hydroxy methoxy polyol was prepared from epoxidation and hydroxylation process, and called as hydroxyl methoxy glycerolmonostearate (HMGMS) polyol. Synthesis process of rigid polyurethane foam was conducted by reaction between HMGMS polyol and methylene diphenyldiisocyanate (MDI) via one shoot process in the presence of additive i.e. ethylene glycol (chain extender), silicon glycol (surfactant), dimethylcyclohexylamine (amine catalyst), stannous octoate (organometalic catalyst) and water as blowing agent. In this work, we investigated the effect of NCO/OH ratio (1.8 ; 2.0 ; 2.2 ; 2.4) and mold system (closed mold and open mold) on the physical and mechanical properties of rigid polyurethane foam. The physical and mechanical properties of rigid foam were conducted by determining the bulk density, dimensional stability, degree of water absorption and compressive strength. It was found out that NCO/OH ratio and mold type were important variables in making RPUF. Key words :